2016
DOI: 10.4314/tjpr.v15i7.11
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and cytotoxic properties of isoprenoids from the red sea soft coral, <i>Lobophytum</i> sp

Abstract: (IZD,(7)(8)(9)(10)(11) MIC ≥ 30 μg/mL). In addition, only diterpene compound (4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The NMR data for compound 9 are presented in this paper. The other known compounds, which are piperine ( 10 ) [22], methyl piperate ( 11 ) [23], piperanine ( 12 ) [24], pipernonaline ( 13 ) [25], piperchabamide B ( 14 ) [9], piperolein-B ( 15 ) [22], 3-phenyl-1-(piperidin-1-yl)propan-1-one ( 16 ) [17] ( E )-3-phenyl-1-(piperidin-1-yl)prop-2-en-1-one ( 17 ) [17], trans -fagaramide ( 18 ) [26], pipercide ( 19 ) [27], guineensine ( 20 ) [27], dihydropiperlonguminine ( 21 ) [25], 5,6-dihydro-1 H -pyridin-2-one ( 22 ) [28], 3-chloro-4-hydroxy-2-piperidone ( 23 ) [29], octahydro-4-hydroxy-3 α -methyl-7-methylene- α -(1-methylethyl)-1 H -indene-1-methanol ( 24 ) [30], alismoxide ( 25 ) [31] (4 S, 4a S, 6 S, 8a S )-octahydro-4-hydroxy-4,8a-dimethyl-6-(1-methylethenyl)naphthalen-1( 2H )-one ( 26 ) [16], ent -4(15)-eudesmene-1 β ,6 α -diol ( 27 ) [32], methylsalicylate-2- O - β - d -glucopyranoside ( 28 ) [33], rozin ( 29 ) [19], piperchabaoside A ( 30 ) [20] (6 S ,9 R )-roseoside ( 31 ) [34], and 2′- O -methyluridine ( 32 ) [35], were identified by comparing their spectroscopic data with those in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The NMR data for compound 9 are presented in this paper. The other known compounds, which are piperine ( 10 ) [22], methyl piperate ( 11 ) [23], piperanine ( 12 ) [24], pipernonaline ( 13 ) [25], piperchabamide B ( 14 ) [9], piperolein-B ( 15 ) [22], 3-phenyl-1-(piperidin-1-yl)propan-1-one ( 16 ) [17] ( E )-3-phenyl-1-(piperidin-1-yl)prop-2-en-1-one ( 17 ) [17], trans -fagaramide ( 18 ) [26], pipercide ( 19 ) [27], guineensine ( 20 ) [27], dihydropiperlonguminine ( 21 ) [25], 5,6-dihydro-1 H -pyridin-2-one ( 22 ) [28], 3-chloro-4-hydroxy-2-piperidone ( 23 ) [29], octahydro-4-hydroxy-3 α -methyl-7-methylene- α -(1-methylethyl)-1 H -indene-1-methanol ( 24 ) [30], alismoxide ( 25 ) [31] (4 S, 4a S, 6 S, 8a S )-octahydro-4-hydroxy-4,8a-dimethyl-6-(1-methylethenyl)naphthalen-1( 2H )-one ( 26 ) [16], ent -4(15)-eudesmene-1 β ,6 α -diol ( 27 ) [32], methylsalicylate-2- O - β - d -glucopyranoside ( 28 ) [33], rozin ( 29 ) [19], piperchabaoside A ( 30 ) [20] (6 S ,9 R )-roseoside ( 31 ) [34], and 2′- O -methyluridine ( 32 ) [35], were identified by comparing their spectroscopic data with those in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the main constituents of the EO from the leaves of C. matourensis, some of them, e.g., β-caryophyllene, cembrene, p -cymene, and β-elemene, have been reported as cytotoxic agents [ 22 , 25 , 26 , 27 , 28 ], indicating that the mixture of them are associated with the cytotoxic and antitumor properties of this EO.…”
Section: Discussionmentioning
confidence: 99%
“…These bioactive compounds showed various pharmacological activities such as antimicrobial, anti-inflammatory and cytotoxic (Putra et al, 2016). Previously, our study on soft corals of Sarcophyton trocheliphorum and lobophytum sp have found numerous secondary metabolites possessing antibacterial and antitumor activities Al Footy et al, 2016). In continuing our focus research on marine organism, particularly from Indonesian marine, our study now starting on soft corals collected off Togean Islands, located in Tojo Una-una, Central Sulawesi.…”
Section: Introductionmentioning
confidence: 92%